Isolation And Characterization Of Native Fluorescent Pseudomonas From Rice Fields Of Assam (India) (Applied Biological Research, 2017)
In present study ten isolate of Pseudomonas, isolated from rice rhizosphere,haracterized on the basis of morpho-biochemical and molecular characteristics. Screening of their plant growth promoting activities viz.,  siderophore production, proteolytic activity, ammonia production, IAA  production and HCN production revealed that the isolate PfAs1 was most  promising one with highest siderophore production (6.18 cm dia. of yellow  halo) and proteolytic activity (5.85 cm dia. halo zone). The results showed that  none of the isolates possessed all the tested PGP activities. IAA and ammonia  production was determined quantitatively for all the isolates. The IAA and ammonia production in tested Pf strains ranged from 15.66 to 48.58 and  179.05 to 394.72 mg L-1. The phylogenetic analysis using 16S rRNA gene  sequences showed phylogenetic position of different fluorescent Pseudomonads. The results revealed that the isolated strains were  Pseudomonas fluorescens and P. putida.
Keywords: PGPR; proteolytic activity; Pseudomonas, rhizosphere; rice; siderophore